2013
DOI: 10.3139/120.110448
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Process Parameters on the Recycling Efficiency of Used Aluminium Beverage Cans (UBCs)

Abstract: In this paper, the effects of process parameters on the recycling efficiency of used aluminium beverage cans (UBCs) were investigated. In the experimental studies, separated internal workshop scraps and used aluminium beverage cans are used as charge materials for melting process. Aluminium beverage cans are thin walled parts and produced with high Mg content aluminium alloys. Thus its high oxidation affinity reduces recycling efficiency of the cans. Used can pieces were pressed to obtain briquettes for chargi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
0
7
0
3
Order By: Relevance
“…Hasil penelitian dengan variasi waktu tahan diperlihatkan pada Gambar 2. , 2011;Alsaffar, 2008;Totten, 2003;ASM vol.2, 2004;Cabden, 1994;Wotton, 1994;Ozer, 2013;Rabah, 2013). Scrap kaleng minuman dilebur dalam keadaan telah dipotong menjadi beberapa bagian kecil dan dicampur antara bagian tutup kaleng dengan badan kaleng.…”
Section: Kadar Magnesiumunclassified
See 1 more Smart Citation
“…Hasil penelitian dengan variasi waktu tahan diperlihatkan pada Gambar 2. , 2011;Alsaffar, 2008;Totten, 2003;ASM vol.2, 2004;Cabden, 1994;Wotton, 1994;Ozer, 2013;Rabah, 2013). Scrap kaleng minuman dilebur dalam keadaan telah dipotong menjadi beberapa bagian kecil dan dicampur antara bagian tutup kaleng dengan badan kaleng.…”
Section: Kadar Magnesiumunclassified
“…Berdasarkan hipotesa dalam penelitian ini semakin banyak penambahan massa flux pada leburan logam maka nilai persen recycling efficiency akan semakin menurun, pernyataan ini juga diperkuat dengan adanya penelitian yang dilakukan oleh Gokhan Ozer dkk pada tahun 2013 dengan hasil maksimum dari penambahan massa flux berada pada penambahan 5% flux dari total massa scrap yang digunakan dan menyatakan bahwa penambahan flux lebih dari 5% akan menurunkan persentase recycling efficiency (Ozer, 2013 intersisial, keadaan ini hanya dapat dilakukan jika atom relatif lebih kecil dibandingkan dengan atom matriks. Jika atom lebih besar dibandingkan dengan atom matriks maka akan menghasilkan distorsi yang sangat besar jika melawati satu bagian intersisi ke intersisi yang lain.…”
Section: Gambar 3 Pengaruh Massa Flux Terhadap Persen Recycling Efficunclassified
“…To increase the reactivity of the flux and the removing efficiency of inclusions from the melts, cryolite or other fluorides may be added, such as Na 3 AlF 6 , CaF 2 , Na 2 SiF 6, that accelerate the wettability with oxides and inclusions. In this way, the magnesium removal from the aluminum scrap is enhanced and the aluminum recovered from the dross is increased [78].…”
Section: Charging and Fluxingmentioning
confidence: 99%
“…Mehrabian [17] shown experimentally how trapped air bubble can result in breakaway oxidation and illustrated this mechanism impeccably. Ozer [18] and Bhagyanathan [19] studied the recycling efficiency of aluminum cans and showed that oxidation during remelting is the key parameter for improved melt cleanliness.…”
Section: Introductionmentioning
confidence: 99%